FREQUENCY OF DIABETES MELLITUS IN PATIENTS WITH ACUTE KIDNEY INJURY UNDERGOING CORONARY ARTERY BYPASS GRAFTING - Baigum, Nusrat; Tasneem, Syeda Sidra; Allah Ditta, Kalsoom; Israr, Wajiha (Journal of Ayub Medical College Abbottabad, 2019)
Background: Diabetes mellitus has a major role in developing acute kidney injury (AKI) in patients undergoing coronary artery bypass grafting (CABG). The study was conducted with the aim to determine the frequency of diabetics in patient developing AKI among patients undergoing CABG. Methods: This cross-sectional study included 120 consecutive patients from Punjab Institute of Cardiology who underwent CABG from March 2018 to May 2018. At the end 101 patients were included for analysis as the rest had missing data. SPSS 20.0 was used to analyse the data. Results: A total of 101 patients were analysed among whom, 52% developed AKI, 34 (33.6%) of the patients with co-morbidity of diabetes mellitus developed acute kidney injury whereas 20 (19%) of the patients without diabetes mellitus developed AKI (Odds Ratio=2.5, 95% CI 1.04 to 6.05, p=0.024).Conclusion: The study concluded that the risk of AKI is significantly higher among patients with diabetes mellitus undergoing CABG. Keywords: Acute kidney injury (AKI); Coronary arteries bypass grafting (CABG); Diabetes mellitus